The Work Engagement Among Nurses in an Urban-Based Tertiary Hospital - Ampan Vimonvattana; Nontawat Benjakul (Nursing Reports, 2025)
Background: Work engagement is essential to the well-being of nurses and the quality of health care, particularly in high-demand urban hospital environments in Bangkok. To determine the levels of work engagement—vigor, dedication, and absorption—among nurses in a Thai urban tertiary hospital, and to identify associated demographic and occupational predictors. Materials and Methods: A cross-sectional study was conducted among 650 nurses at a tertiary university hospital in Bangkok, Thailand, from February to March 2025. Participants were selected through simple random sampling. They completed an online survey including demographic data and the Utrecht Work Engagement Scale (UWES), which assesses three dimensions of engagement: vigor, dedication, and absorption. To identify the predictors of high engagement levels, chi-square tests and multivariate binary logistic regression were used. Results: Most nurses reported low engagement across all dimensions: 73.1% for vigor, 69.1% for dedication, and 70.0% for absorption. In the adjusted models, monthly income was a significant predictor of higher vigor and dedication, whereas no significant predictors emerged for absorption. Other variables, including age, experience, and professional rank, were significant in the bivariate analyses but not in the multivariate models. Conclusions: Nurse engagement remains suboptimal in the urban tertiary hospital setting, with financial compensation emerging as a key determinant. Strategic interventions to improve income equity and career development may help enhance engagement and retention in the nursing workforce.